Interrrogating a Framework for Universal Social Protection in India - Srivastava, Ravi (Southern Centre for Inequality Studies (SCIS), 2021)
The paper begins by dealing with conceptual issues around social security, social protection, and a social protection floor and argues for a rights based social protection floor for India. It then describes the broad social security or social protection system in place in the country. Since social protection systems are contingent on the characteristics and nature of work and employment relations, the paper uses existing data sources to elaborate on the (gendered) nature of the workforce. It also points out how existing social security systems reinforce labour market inequalities. The paper goes on to discuss the nature of expansion of social security and social protection since the turn of the century. It describes two distinct phases: the first, from about 2002 to 2014 when these systems expanded due to grassroots movements, court judgments and government responses; the second, from 2014 onwards, when the new government turned its back on rights based social security, but populist pressures still led to the introduction of new measures, although the financial priority given to social protection declined. Finally, the paper focuses on the current issues and challenges in moving towards a rights based social protection floor in India. It argues that such a social protection floor should combine worker-centric and citizen-centric features and comprise minimum guarantees for all at the base, with a second level of contributory social security. It considers the possible options for social protection – contributory and non-contributory and a universal basic income. It also analyses the consequences of the government’s thrust on digital financialisation for benefit payments and on biometric identification of workers and argues that, while the introduction of a social security registration system for workers is essential, approaches currently being put in place impose high costs on the poorest, and do not build on adequate data privacy safeguards.
Keywords: Future of workers; Social security; Social protection; Social protection floor; Worker-centric; Citizen-centric; Digital financialisation; Biometric identification of workers; Universal Social Protection in India